Bridging the Gap to 6G: Leveraging the Synergy of Standardization and Adaptability - Kulkarni, Anjanabhargavi; Goudar, R.H.; Vinayak B., Joshi; H.T., Harish (EAI Endorsed Transactions on Scalable Information Systems, 2024)
The field of wireless network and communication technology is evolving from generation to generation from 1G to 6G as of now till expected to be deployed and used by 2030. It is to succeed in 5G and bring significant improvements in terms of connectivity, speed, and size in next-generation communication technology. 6G aims to deal with the rising need for more rapid information speed, low latency, and wider network coverage. This intelligent communication is proposed to meet these demands and enable new services and applications. This review paper highlights the key enablers and challenges involved in implementing intelligent communication beyond 5G. The paper identifies the research gaps for incorporating beyond 5G communication networks and outlines the possible 6G key objectives from a flexibility standpoint. It reviews infrastructure deployment, network densification, spectrum capacity and network energy efficiency in predecessors to 6G. This paper emphasizes the need for standardization and adaptation of research areas to revolutionize 6G wireless communication, focusing on areas like, ultra massive MIMO, Terahertz Communications, Cell-Free Communications, Intelligent Reflecting Surface, Visible Light Communication, Internet of Things, Big Data management, Artificial Intelligence, and network connectivity techniques.
Keywords: 6G; Cell-Free Communications; Internet of Things; Intelligent Reflecting Surface; massive MIMO; Terahertz Communications; Visible Light Communication